UTX (KDM6A) promotes differentiation noncatalytically in somatic self-renewing epithelia - Gina N. Pacella; Nina Kuprasertkul; Lydia Bao; Sijia Huang; Carina D’souza; Stephen M. Prouty; Amy Anderson; Alexandra M. Maldonado López; Morgan Sinkfield; Cyria Olingou; John T. Seykora; Brian C. Capell (Proceedings of the National Academy of Sciences, 2025)
The X-linked histone demethylase, UTX ( KDM6A ), is a master regulator of gene enhancers, though its role in self-renewing epithelia like the skin is not well understood. Here, we find that UTX is a key regulator of skin differentiation via the regulation of retinoic acid (RA) signaling, an essential metabolic pathway in both skin homeostasis, as well as in the treatment of an array of skin conditions ranging from cancer and acne to aging. Through deletion of Utx in the skin, we demonstrate direct regulation of both retinoid metabolic genes such as Crabp2 , as well as key genes involved in epidermal stem cell fate and differentiation (i.e., Cdh1 , Grhl3 , Ctnnb1 ). Spatial analyses show that UTX loss dysregulates epidermal, sebaceous, and hair follicle differentiation programs. Strikingly, this only occurs in homozygous females, demonstrating that UTX’s Y-linked paralog, UTY ( Kdm6c ), can compensate in males. Further, we observe genome-wide losses of H3K27 acetylation (H3K27ac) with minimal changes in H3K27 trimethylation (H3K27me3), revealing that UTX functions primarily noncatalytically to promote skin homeostasis. Together, the elucidation of these links between epigenetics, metabolic signaling, and epithelial differentiation offers new insights into how epigenetic modulation may allow for fine-tuning of key signaling pathways to treat disease.